An analysis of grass-roots co-operative economic development in Nova Scotia and Caribbean missions (1930-1960) : case studies in the light of Catholic social teaching and social capital theory - Bouzigard, MA (2006)
In contrast to research studies, which approach Catholic social teaching (CST) as a theoretical complex, abstracted from situations in which it was applied, this thesis deliberately adapts an inductive method. Through this contextual approach attention devoted to specific co-operative projects exemplifies the extent of CST’s influence. Missionary pioneers created new socioeconomic practices and mutual-aid (voluntary) associations; consequently, these democratic, co-operative practices not only enhanced social capital formation from below but also implicitly challenged a top-down formulation of the social teaching. Thus, this thesis not only analyses specific examples of grass-roots development but also intentionally approaches CST via these specific exemplifications rather than vice versa. These co-operative development projects through self-help, communitarian practices within a social capital-social justice nexus privileged the acting person over dominant collective action, offering an alternative for economic development in tension with both nationalist socialism and liberal capitalism. Five empirical cases, primarily analysing original archival sources, demonstrate an historical interplay between formation of social capital practices and an enactment of CST principles for social justice within co-operative movements. Major findings indicate that social capital, although varied in each case, significantly contributed toward organisational capacities in sustaining grass-roots co-operative practices. Enacting social justice principles, however, proved much more complex in actuality due to divergence, tension, or conflict between multiple government, private and religious-sponsored co-operative sectors.